The Dialectic of Agrarian Justice: A Jurisprudential Analysis of Unlawful Acts in Land Disputes from the District Court to Judicial Review - Wijaya, Laela Kuwayyis; Rahma, Nasya Nadhira; Ghifari, Tyazza Amaranila (CV. Social Politic Genius (SIGn), 2025)
Inconsistency in court decisions on agrarian disputes presents a crucial problem that tests the balance between formal legal certainty and substantive justice. This research aims to conduct an in-depth analysis of the application of the elements of an unlawful act and the dialectic of judicial reasoning (ratio decidendi). The analysis is conducted in the context of an ownership dispute over a 14,000 m² parcel of land in East Kutai. This case traversed four judicial tiers, from the District Court to the Judicial Review at the Supreme Court. Employing a normative legal research method through a case study approach, a comparative-qualitative analysis of each court decision is performed to dissect the legal logic underlying the dynamics of the contradictory verdicts. The findings indicate that the Supreme Court, in its role as the judex juris, ultimately affirmed the superiority of material truth. This truth, proven by actual and good-faith physical possession, was deemed superior to the legal formalism embodied in substantially flawed ownership documents. The substantive-justice-oriented court decision of First Instance was annulled at the formalistic Appeal level, only to be restored by the Supreme Court at the Cassation level and subsequently upheld in the Judicial Review stage. It is concluded that the final decision in this case not only provides concrete legal protection for the good-faith land possessor but also contributes significantly to jurisprudence as an important precedent that reinforces the judiciary’s orientation toward achieving substantive justice in the resolution of agrarian disputes in Indonesia.